2015
DOI: 10.1007/s10071-015-0842-8
|View full text |Cite
|
Sign up to set email alerts
|

Domestic pigs’ (Sus scrofa domestica) use of direct and indirect visual and auditory cues in an object choice task

Abstract: Recently, foraging strategies have been linked to the ability to use indirect visual information. More selective feeders should express a higher aversion against losses compared to non-selective feeders and should therefore be more prone to avoid empty food locations. To extend these findings, in this study, we present a series of studies investigating the use of direct and indirect visual and auditory information by an omnivorous but selective feeder-the domestic pig. Subjects had to choose between two bucket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Although pigs could solve the tasks, it was unclear whether they simply relied on stimulus enhancement cues (i.e., the slope of the board and the shaking movement or noise of the cup). Nawroth and von Borell (24) repeated the latter task that used a shaking bucket with a modified setup. Here, pigs were tested in their ability to use indirect visual and auditory stimuli (i.e., the absence of visual or acoustic cues) by choosing between two potential hiding locations.…”
Section: Cognitive Studies In Livestock Animalsmentioning
confidence: 99%
“…Although pigs could solve the tasks, it was unclear whether they simply relied on stimulus enhancement cues (i.e., the slope of the board and the shaking movement or noise of the cup). Nawroth and von Borell (24) repeated the latter task that used a shaking bucket with a modified setup. Here, pigs were tested in their ability to use indirect visual and auditory stimuli (i.e., the absence of visual or acoustic cues) by choosing between two potential hiding locations.…”
Section: Cognitive Studies In Livestock Animalsmentioning
confidence: 99%
“…However, weaning at 21 days of age is common practice in most pig farming areas. The other strategy is inspired by the fact that pigs are known to be good learners, whether in trials associated with food delivery ( Gieling, Nordquist, & van der Staay, 2011 ) or through repetition ( Nawroth & von Borell, 2015 ). This strategy would use the pigs’ natural ability by ‘training’ them to interact with the rope.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find learning patterns between test sessions, which corresponded to our expectation as we did not want piglets to learn but wanted to test their spontaneous behaviour. Nawroth and von Borell [45] reported that piglets needed up to 72 or 84 trials to reach the success criterion using visual or auditory signals respectively in the same sessions of a test. This large number of trials would be closer to a training process instead of simply testing pigs’ spontaneous inter-specific communicational capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Olive baboons ( Papio anubis ) also performed begging gestures to obtain a reward from an experimenter even though they did not belong to the group trained to use this gesture. Piglets are known to be good learners in tasks associated with food delivery [44] and are able to learn through the course of experiments [45]. However, the spontaneous use of human pointing gestures and/or auditory signals reported in piglets, as well the effect of experience on their response still need attention.…”
Section: Introductionmentioning
confidence: 99%